The diagnosis of endometrial cancer in women with asymptomatic endometrial polyp does not increase survival rates: an israel gynecologic oncology group study. (June 2021) - Namazov, Ahmet; Helpman, Limor; Eitan, Ram; Vaknin, Zvi; Lavie, Ofer; Ben-Arie, Alon; Amit, Amnon; Levy, Tally; Volodarsky, Michael; Atlas, Ilan; Bruchim, Ilan; Gemer, Ofer
Highlights: This retrospective study examined the early diagnosis of malignant endometrial polyp in asymptomatic women. No difference in survival outcomes was evident between women who experienced bleeding and those who did not. In the absence of factors indicating a high risk of endometrial cancer, clinical and sonographic follow-up is the advised management strategy for these patients. abstract: Objective: To compare outcomes of symptomatic and asymptomatic women with endometrial cancer and a preoperative diagnosis of an endometrial polyp. Design: An Israel Gynecologic Oncology Group multi-center retrospective cohort study. Methods: Of 635 patients with endometrial cancer and a preoperative diagnosis of an endometrial polyp who underwent surgery between 2002 and 2014 in one of 11 centers in Israel were divided into two groups according to the presence of bleeding symptoms. Outcome measures included recurrence-free survival, disease-specific survival and overall survival. Survival data were plotted according to the method of Kaplan and Meier and compared using the log-rank test. Results: There were 513 symptomatic and 122 asymptomatic women with endometrial cancer and a preoperative diagnosis of an endometrial polyp. The median follow-up was 52 months (range 12-120 months). There were no differences between patients who experienced bleeding and those who did not in 5-year recurrence-free survival (85.2 % vs. 85.7 %; p=0.83, respectively), disease-specific survival (88.2 % vs. 89.2 %; p=0.71, respectively), or overall survival (80.2% vs. 78.4 %; p=0.97, respectively). Conclusion: The diagnosis of endometrial cancer in patients with asymptomatic endometrial polyps is not associated with improved outcomes as compared with patients with bleeding. In the absence of factors indicating a high risk of endometrial cancer, clinical and sonographic follow-up is the advised management strategy for these patients.